INFLUENCE OF SINGLE AND COMBINED ABIOTIC STRESS ON CHANGES IN THE BIOSYNTHESIS OF ENZYMATIVE ANTIOXIDANTS IN CHENOPODIUM QUINOA L. (Experimental biology, 2024)
Plants adapted to high insolation and dry conditions exhibit high enzyme activity (SOD). Activation of antioxidant enzymes such as superoxide dismutase (SOD) plays a key role in reducing oxidative stress in quinoa plants. In chloroplasts, where photosynthesis occurs, reactive oxygen species appear. The level of SOD activity increases with water and nutrient deficiency, indicating activation of chloroplast antioxidant defenses even before the appearance of visible signs of physiological stress. The transition from a normal state to a stressful one probably leads to a suppression of antioxidant processes, accompanied by a decrease in SOD activity. Ultimately, a set of secondary metabolites are formed in quinoa, capable of synthesizing various compounds with a wide spectrum of biological activity.This abstract presents the results of studies of changes in the activity of enzymatic antioxidants such as superoxide dismutase and peroxidase in young Chenopodium quinoa L plants in response to osmotic, salt and combined stress. The findings demonstrate a link between the level of antioxidant defense in the Chenopodium quinoa L system and its ability to cope with various types of stress. Results obtained from the combined exposure of young quinoa plants to 200 mM NaCl + PEG indicate a transition from eustress to distress in young quinoa plants.
Keywords: quinoa, enzymatic antioxidants, osmotic stress, salt stress, combined stress, eustress, distress